Optimization of Grid-Connected PV Systems: Balancing Economics and Environmental Sustainability in Nigeria - Usman, Habib Muhammad; Sharma, Nirma Kumari; Joshi, Deepak Kumar; Sani, Baba Isah; Mahmud, Muhammad; Saminu, Sani; Yero, Abdulbasid Bashir; Auwal, Rabiu Sharif (Universitas Ahmad Dahlan, 2024)
Nigeria faces the dual challenge of harmful industrial emissions contributing to climate change and unreliable power supply, demanding urgent attention. This study focuses on optimizing a grid-connected photovoltaic (PV) system at the Department of Electrical Engineering, Ahmadu Bello University Zaria, Kaduna, Nigeria, with the goal of achieving economic and environmental sustainability. The study utilizes HOMER, a widely used optimization tool for renewable energy systems, to design and evaluate three distinct energy scenarios. The first scenario relies solely on grid power, resulting in high annual costs of 2,838, significant environmental degradation, and zero renewable energy contribution. The second scenario integrates solar PV with grid power, reducing grid dependency but only partially addressing cost and environmental concerns, with an annual energy cost of 2,714 and 1,867 kWh generated from solar PV. The third scenario demonstrates the most favourable outcomes, combining high solar PV generation with economic benefits. The system produces 29,684 kWh annually, selling 521 worth of surplus energy back to the grid, resulting in a net yearly energy cost of 1,043. The initial installation cost is expected to be recovered within two years, offering potential savings of 20,000 over the system's 20-year lifespan. These findings show the viability of solar PV systems as a solution to Nigeria's energy challenges, underscoring the importance of balancing economic and environmental factors in energy system design. The study provides valuable insights for institutions and similar contexts looking to transition to more sustainable energy systems.